Improving Teacher Professionalism Through Managerial Principals At The Muadalahwustho Education Unit, Darussalam Islamic Boarding School, Blokagung, Banyuwangi - Muhammad Irfan Fauzi (Publikasi Indonesia, 2023)
The objectives in this study are as follows: (1) To describe and study more deeply about the principal's management in improving teacher professionalism in the Muadalah, Wustho Al-Amiriyah Ponpes Darussalam Blokagung Education Unit (2) To describe the principal's managerial steps in improving the professionalism of teacher teachers in the Muadalah, Wustho Al-Amiriyah Ponpes Darussalam Blokagung Education Unit. The data collection used in this study was observation, interviews and documentation. This type of research is in the form of qualitative research. Data is analyzed in the form of data reduction, data presentation and conclusions. By design take data sources on principals and teachers. The results showed that the managerial principal of the Mudari Wustho Al-Amiriyah Blokagung Education Unit consisted of 1. planning, 2. implementation, 3. surveillance, 4. Organizing. The principal as manager plays the role of 1. educator, 2. manager, 3. supervisor, 4. motivators, 5. Innovator. The managerial steps taken by the principal are to carry out 1. supervision, 2. give rewards, 3. motivating 4. encourage continuing further education. For this reason, researchers concluded that the principal as a manager carries out his duties well to improve teacher professionalism can be seen from how the principal makes efforts to improve teacher professionalism